2018
DOI: 10.1186/s40468-018-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

How does anxiety influence language performance? From the perspectives of foreign language classroom anxiety and cognitive test anxiety

Abstract: This study examined the relationships between students' foreign language classroom anxiety and cognitive test anxiety and their College English Test Band 4 (CET-4) performance. A questionnaire was distributed to 921 Chinese university students to understand the nature and degree of the examined relationships. Follow-up interviews with 12 students were used to shed further light on uncovering mechanisms of relationships found in the survey. Results revealed three factors of anxiety, explaining 43. 14% of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 45 publications
4
81
1
2
Order By: Relevance
“…The structural equation modeling run to answer the first question of the study indicated that all components of speaking were lower than 0.30, showing significance and they all, were in a negative and significant correlation with anxiety, the sample size was adequate for running the model and the structural regression model enjoyed a good fit to show that the components of speaking had significant contributions to their latent variable and all components of speaking performance were in a negative correlation with anxiety. These results are consistent with those of other researchers (Mazouzi, 2013;Thornbury, 2005;Woodrow, 2006;Brown, 2000;Mahripah, 2014;Tanveer, 2007;Kayaoğlu & Sağlamel, 2013;Hanifa, 2018;Baran-Łucarz, 2013;Mahmoodzadeh, 2012;Suleimenova, 2013;Dewaele & Ip, 2013;Leong & Ahmadi, 2017;Subekti, 2018;Zheng & Cheng, 2018;Liu, 2018), which found significant negative relationships between the anxiety and speaking performance. Conversely, the other two components of vocabulary and grammar as components more related with writing should take a different route and not be so affected by anxiety.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…The structural equation modeling run to answer the first question of the study indicated that all components of speaking were lower than 0.30, showing significance and they all, were in a negative and significant correlation with anxiety, the sample size was adequate for running the model and the structural regression model enjoyed a good fit to show that the components of speaking had significant contributions to their latent variable and all components of speaking performance were in a negative correlation with anxiety. These results are consistent with those of other researchers (Mazouzi, 2013;Thornbury, 2005;Woodrow, 2006;Brown, 2000;Mahripah, 2014;Tanveer, 2007;Kayaoğlu & Sağlamel, 2013;Hanifa, 2018;Baran-Łucarz, 2013;Mahmoodzadeh, 2012;Suleimenova, 2013;Dewaele & Ip, 2013;Leong & Ahmadi, 2017;Subekti, 2018;Zheng & Cheng, 2018;Liu, 2018), which found significant negative relationships between the anxiety and speaking performance. Conversely, the other two components of vocabulary and grammar as components more related with writing should take a different route and not be so affected by anxiety.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…Anxiety is identified as a distinct affective variable in second language research. According to Tanveer (2007) as cited by Zheng and Cheng (2018) that feeling of anxiety is one of the commonly expressed by second/foreign language learners in the learning speaking a second/foreign language and also considered to exert a negative effect on communication to the target language.…”
Section: English Language Anxietymentioning
confidence: 99%
“…Horwitz, Horwitz and Cope (1986) defined foreign-language classroom anxiety as "a distinct complex of self-perceptions, beliefs, feelings, and behaviours related to classroom language learning arising from the uniqueness of the language learning process" (p. 128). Studies in the literature have reported a negative correlation between high levels of anxiety and language achievement and performance (Demirdaş & Bozdoğan, 2013;Hewitt & Stephenson, 2012;Salehi & Marefat, 2014;Woodrow, 2006;Zheng & Cheng, 2018). The influence of FLA on academic performance in a foreign language is quite complex, that is, students with high levels of FLA generally exhibit a lower level of proficiency in English, whereas low achievement could be also a cause of FLA (Trang, Baldauf Jr., & Moni, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, three different measures were used to reflect students' learning-related beliefs and strategies, and it was hypothesised that these constructs would help us to predict the attendance rates and academic performance which students have at the end of the autumn term. A vast number of studies have identified FL self-efficacy (Bai et al, 2019;Ferla, Valcke & Cai, 2009;Honicke & Broadbent, 2016;Mills et al, 2007;Sarıçoban & Behjoo, 2016) and FLA (Hewitt & Stephenson, 2012;Woodrow, 2006;Zheng & Cheng, 2018) as predictors of academic performance. Based on the findings of some studies from different educational settings (Bai et al, 2019;Honicke & Broadbent, 2016;Raoofi et al, 2012), it was also hypothesised that selfefficacy would be the strongest predictor of academic achievement.…”
Section: Introductionmentioning
confidence: 99%